The Doctrine of Illegality and Interference with Chattels - Goudkamp, J; Mayr, L (Hart Publishing, 2015)
The doctrine of illegality is now in vogue as an answer to liability in tort. It is also very regularly discussed by scholars. It has generated a literature that is large enough to justify the publication of a bibliography. However, the attention that has been lavished on the doctrine as it operates within tort law has largely been confined to the context of actions for negligently inflicted personal injury. The doctrine?s role in other situations within tort law has been neglected. This chapter begins the process of redressing this situation. It does so by analysing the doctrine in relation to actions for interference with chattels. We postulate a wide range of hypothetical cases and consider how these cases would be decided if they arise. This discussion reveals the existence of significant lacunae in this area of the law, with no authority that provides definitive guidance as to whether the doctrine applies in particular situations. We also ask, in the in relation to those cases that would fail on the ground of illegality, what the precise legal route is by which that result is achieved. Finally, we investigate how the hypothetical cases ought to be decided. We contend that what little law there is on the doctrine of illegality in the chattels context sometimes produces the wrong outcome and, where it delivers the right outcome, it frequently does so for the wrong reasons.